Mother's Eating Style, Breakfast Habits, Fruit and Vegetable Consumption in Early Childhood in TK Al Amien Jember - Adi, Dhuha Itsnanisa; Permatasari, Elok; Oktafiani, Lirista Dyah Ayu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Good nutritional intake in early childhood can help maintain a child's immune system so that it is not easily exposed to infectious diseases, especially during the Coronavirus Disease (COVID-19) pandemic like today. Parenting by mothers plays an important role in how nutritional intake in children can be fulfilled. This study aims to describe the mother's eating style, breakfast habits, and fruit and vegetable consumption in early childhood. This study is a descriptive study conducted on 36 parents of early childhood in Al Amien Jember Kindergarten. This research has received ethical approval from KEPK FKG UNEJ No. 1171/UN25.8/KEPK/DL/2021. The results of research on eating patterns, it is known that in most early childhood 83.3% always have breakfast every day. Nevertheless, Most early childhooders consume vegetables and fruits less than 3 times a day. The results of research on maternal parenting showed that as much as 50%. 44.4% of mothers sometimes apply parenting by forcing children if the child refuse food that is usually consumed. Even though the dietary consumption pattern in this study is quite good, there needs to be further education about parenting, and feeding, especially the provision of balanced nutritious foods and diverse foods.